PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN MENGGUNAKAN METODE BERMAIN PERAN - Dalima, Dalima (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Base on experience that citizenship education can’t grew students caracter. So that this research express and describe increase students learn result of Citizenship Education whit use Role Play method for the five class of 09 Bahagia Padang Gelugur Elemtery School. This type of research used Research Action Class (PTK) method whit aproach qualitative and quantitative. Research obyect is learn result, data collection is done through observation, space note, documentation and learn result. Data analysis was done from planing, execution, inspection, until reflection and conclude. This data reduction based on problem research, data ready, and conclude or verivication. The results showed that the use Role Play method can increase student learn result of Citizenship Education for the five class of 03 Bahagia Padang Gelugur Elemtery School.   Kata Kunci: pendidikan kewarganegaraan, hasil belajar dan metode bermain peran